Policing insurgencies cops as counterinsurgents - Fair, C. Christine; Ganguly, Sumit (Oxford international relations in South Asia series, 2014)
This volume explores a relatively under-researched issue: the role of domestic police forces in contending with insurgency. The cases are drawn from Central, South, and Southeast Asia, as also Africa and the Middle East. Each country-specific chapter is written by a well-established scholar who has spent considerable time in the country of study.